Essentials of HRM - Tyson, Shaun; York, Alfred (Oxford Butterworth-Heinemann, 2000)
Essentials of HRM combines an overview of organisational behavior with a detailed explanation of human resource management policies and techniques, and acts as an introduction to the study of industrial relations, including employment law.
Includes index
rua 25/02/15
Loans
Keywords: Personnel management